Design and Implementation of spacecraft component-level test management system. Issue 5 (June 2019) - Zhang, J; Zheng, H M; Lu, T; Guo, W; Chen, A R; Liu, Y
Abstract: This article is to introduce the typical performance and configuration of component-level environmental test management system. Firstly, the characteristic of spacecraft component-level environmental test is analyzed and the main problems are pointed out. In order to address the shortcomings, the project of the test management system has been envisaged. Then, the composition, structure and implementation method are described. Results show that the management system solves many problems after its application. The system has the function of key parameter monitoring and a timed automatic inspection. It reduces the strength of the workforce and improves the quality of process control. The data packs of the product are enriched too. This system unifies the device drivers and communication methods of multiple manufactures, and completes the whole process automatic control of mechanics, thermal and comprehensive environmental tests. The system adopts the idea of modular design and has the function of convenient expansion. It has been deployed in many laboratories and can be promoted to other industries in the future.